KINERJA SUMBER DAYA MANUSIA DI INDUSTRI KREATIF DIGITAL KOTA BANDUNG - Asti Nur Aryanti (In Search (Informatic, Science, Entrepreneur, Applied Art, Research, Humanism), 2018)
Digital creative industry, one of the creative industry subsector that is prioritized in the third stage of the development of the national creative industry, needs to be developed through collaboration of human resource creativity and technology. One of the efforts of human resource development is improving the performance quality. Therefore, this study aims at providing an overview of the performance of human resources in the digital creative industries in Bandung. Data was collected through interviews and questionnaires on the individual, employee, owner, businessman and manager of each digital companies listed as member of Bandung Digital Valley. Descriptive method was employed to describe the performance variable independently. The results revealed that the performance of human resources in the creative industries in Bandung was in the high category. The dimension that has the highest score was the cooperation and the dimension with the lowest score was the quantity of work. Keyword: Human Resource Performance, Digital Creative Industry